A Stepwise Illustration of the Translabyrinthine Approach to a Large Cystic Vestibular Schwannoma - Nickele, Christopher M (2012)
INTRODUCTION: Of the presigmoid approaches, the translabyrinthine approach is often used when a large exposure is needed to the cerebello-pontine angle, but hearing preservation is not a concern. At our institution, this approach is performed in collboration with ENT/Otolaryngology for temporal bone drilling and exposure. METHODS: In this video and paper, we demonstrate the use of the translabyrinthine approach for resection of a large cystic vestibular schwannoma, delineating the steps of positioning, opening, temporal bone drilling, tumor resection and closure. RESULTS: Gross total resection was obtained in this patient. His postoperative facial function was House-Brackmann grade II on the side ipsilateral to the tumor, although this improved with time. CONCLUSION: The translabyrinthine approach to the cerebello-pontine angle is an excellent approach for masses that extend toward the midline or anterior to the pons. Although hearing is sacrificed, facial nerve function is generally spared.